INDICATORS OF COAGULATION HEMOSTASIS AND DEGREE OF BLOOD OXYGENATION IN RATS UNDER THE OPIOID INFLUENCE IN THE LATE TERMS OF CORRECTION - Paltov, Ye.V.; Masna, Z.Z.; Kryvko, Yu.Ya.; Войценко, К.І.; Vergun, A.R. (World of Medicine and Biology, 2022)
A long-term use of opioid analgesics is the cause of hematological changes that lead to trophicity and oxygenation disorders of tissues and organs of various body systems. In the study 50 white, sexually mature rats (160–270 g) were used. With the help of generally accepted methods, we investigated the dynamics of changes in hematological indicators of coagulation hemostasis and the degree of oxygenation of the blood of rats in the chronic period of opioid exposure and during correction. Correction was carried out with the Pentoxifylline. The results of our study significantly expand the data on the negative influence of opioids on the body during their long-term use and testify that it leads to the development of significant changes in coagulation hemostasis indicators (number of platelets, prothrombin time, prothrombin index, whole blood recalcification time, total fibrinogen, hemoglobin, hematocrit), which leads to impaired vascularization and progression of the phenomenon of dyscirculatory hypoxia.
Keywords: rheology change; oxygenation disorder; opioid analgesic; rat; chronic period; correction